Thermal Conductivity of FeS and Its Implications for Mercury's Long‐Sustaining Magnetic Field. Issue 9 (3rd September 2019) - Manthilake, G.; Chantel, J.; Monteux, J.; Andrault, D.; Bouhifd, M. A.; Bolfan Casanova, N.; Boulard, E.; Guignot, N.; King, A.; Itie, J. P.
Abstract: The MESSENGER mission revealed that Mercury's magnetic field might have operated since 3.7–3.9 Ga. While the intrinsic magnetism suggests an active dynamo within Mercury's core, the mechanism that is responsible for sustaining the dynamo for prolonged period of time remains unknown. Here we investigated the electrical conductivity of Fe‐S alloys at pressure of 8 GPa and temperatures up to 1, 700 K. We show that the electrical conductivity of Fe‐S alloys at 1, 500 K is about 10 3 S/m, 2 orders of magnitude lower than the previously assumed value for dynamo calculations. The thermal conductivity was estimated using the Wiedemann‐Franz law. The total thermal conductivity of FeS is estimated to be 4 Wm/K at the Mercurian core‐mantle boundary conditions. The low thermal conductivity suggests that a thermally driven dynamo operating on Mercury is more likely than expected. If coupled with chemical buoyancy sources, it is possible to sustain an intrinsic dynamo during time scales compatible with the MESSENGER observations. Plain Language Summary: Mercury's weak magnetic field intensity that persisted over the last 3.9 billion years has long baffled the planetary science community. Various explanations have been proposed; nevertheless, there has been no consensus on how intrinsic dynamo with such weak energetics have existed in Mercury for prolonged period. In our submitted manuscript, we exclusively looked at the electrical and thermal conductivity in Fe‐S alloys, the dominant phase in planet Mercury's outer core. Our results indicate that electrical conductivity of Fe‐S alloys is 2 orders of magnitude lower than the previously assumed value for dynamo calculations. The low thermal conductivity obtained in this study suggests that the heat extraction from Mercury's core through the solid Fe‐S layer is a highly inefficient process. Our estimations suggest the heat‐flux from the core only produces less than 1 TW of energy. The low heat flux prevents the Mercurian core from rapid solidification, sustaining an intrinsic dynamo in Mercury since 3.9 Ga. Key Points: Incorporation of S significantly reduces both electrical and thermal conductivities of FeS The low thermal conductivity of FeS may have prevented the Mercurian core from rapid solidification Mercury dynamo can be driven by both thermal and chemical buoyancy forces